A multi‐institutional retrospective study of carbon‐ion radiotherapy for non‐squamous cell malignant tumors of the nasopharynx: Subanalysis of Japan Carbon‐Ion Radiation Oncology Study Group study 1402 HN. (18th November 2018) - Abe, Takanori; Ohno, Tatsuya; Koto, Masashi; Demizu, Yusuke; Suefuji, Hiroaki; Tsuji, Hiroshi; Okimoto, Tomoaki; Shioyama, Yoshiyuki; Saitoh, Jun‐ichi; Shirai, Katsuyuki; Nemoto, Kenji; Nakano, Takashi; et al.
Abstract: Background: This multi‐institutional retrospective study focused on the clinical outcome of carbon‐ion radiotherapy (C‐ion RT) for non‐squamous cell malignant tumors of the nasopharynx. Methods: The Japan Carbon‐ion Radiation Oncology Study Group collected and analyzed data for 43 patients with non‐squamous cell malignant tumors of the nasopharynx treated with C‐ion RT at four institutions in Japan. Results: Twenty‐nine patients had adenoid cystic carcinomas, seven had malignant melanomas, three had adenocarcinomas, two had mucoepidermoid carcinomas, and two had other pathologies. Twenty‐six of the 43 patients (61%) had T4 tumors. The most common dose‐fractionation schedule was 64 Gy (relative biological effectiveness) in 16 fractions. The median follow‐up period was 30 months. The 2‐year local control (LC) and overall survival (OS) rates were 88% and 84%, respectively. For late toxicity, one patient developed grade 4 optic nerve disorder and two developed grade 5 pharyngeal hemorrhage. Actual incidence of grade 3 or higher late adverse events was 19%, and included cranial nerve dysfunction, jaw bone necrosis, central nervous system necrosis, and ear inflammation. Conclusions: C‐ion RT provided good LC and OS rates with acceptable toxicity for treatment of non‐squamous cell malignant tumors of the nasopharynx. Abstract : This is the first study of 43 patients with non‐squamous cell malignant tumors of the nasopharynx treated with carbon‐ion radiotherapy. Carbon‐ion radiotherapy provided good LC and OS rates with acceptable toxicity even though non‐squamous cell malignant tumors of the nasopharynx often show refractoriness to the conventional therapy.